Angular-of-incidence dependence of total yield of channeling radiation from relativistic electrons in thin Si and c crystals; Radiation from Relativistic Electrons in Periodic Structures. RREPS-15 - Abdrashitov S. Sergei; Bogdanov O. V. Oleg Viktorovich; Dabagov S. Sultan; Pivovarov Yu. L. Yuriy Leonidovich; Tukhfatullin T. A. Timur Ahatovich (Poster Session, 2015)
Title screen.